Mecanismo de acción de las fosfatasas ácidas de bajo peso molecular - Guija, Emilio (2007)
Acid phosphatases are enzymes widespread in nature that hydrolyze phosphomonoesters at pH 5,0; this reaction yields alcohol and inorganic phosphate. Comparison of bovine, alpaca and porcine liver phosphatases kcat/Km values suggests these enzymes have a high affinity for p-nitrophenyl phosphate substrate. Products that are released during acid phosphatase catalysis show that phenol or p-nitrophenol behave as non competitive inhibitors, whereas inorganic phosphate shows competitive inhibition. Different nucleophiles more efficient than water have been used, such as methanol, ethanol and glycerol, showing the probable formation of a covalent complex in the catalytic sequence. Modifications produced in Km and Vmax values as well as in the reaction released products suggest the development of an enzyme-phosphate complex. pH affects acid phosphatases Km and Vmax values. Behavioral analysis of these enzymes at 3,8 to 6,8 pH range suggests the location of a pKa 6,0 aminoacid residue in the active site. The use of a diethylpyrocarbonate compound which selectively reacts with protein histidine residues completely inhibits this kind of phosphatases. Also, multiple inhibition kinetic survey performed in presence of inorganic phosphate and diethylpyrocarbonate allows a Ki value calculation equal to that obtained in other experimental conditions. In this respect, low molecular weight acid phosphatases would catalyze reactions through a uni biordered model, forming an intermediate covalent complex; histidine residues would directly participate in the catalysis.